THE MIND STRUCTURE OF AN INDEPENDENT WOMAN AS REFLECTED IN CHARLOTTE BRONTE’S NOVEL JANE (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2014)
This study is aimed at (1) describing the character and characterization of Jane Eyre (2) finding the mind structure of Jane Eyre (3) describing a portrait of Jane Eyre as an independent woman. This study is a descriptive qualitative study. The data were analyzed by using psychological approach. The data were gathered by reading the novel thoroughly, identifying, compiling, classifying, selecting, and reporting. The analysis was done by several techniques including the process of exposing, describing, and interpreting. The psychoanalysis theory by Freud was applied in finding the mind structure of Jane Eyre in the novel by finding the Id, the Ego and the Superego. The results were gained, first, Jane is described as a woman who is not beautiful but she has strong characteristics who are mature, smart, hard worker, confident, and generous. Second, the mind structure of Jane Eyre shows that Jane’s id is reflected in a desire to love and to be loved, a desire to be independent and a desire to be acknowledged. However, Jane’s ego is reflected in several actions. They are treating a doll like a human being, resisting or denying everybody who has limited her independence and also being a teacher in order to get the acknowledgement from the society and people around her. Whereas, for the representation of Jane’s superego, she could prove her believes to others. They are; Jane believes that everyone who loves and respects each other will also to get love and respect from others too, then Jane believes that everyone who has fought for the truth should not have to feel guilty and regret, and the last Jane believes that by being a teacher she could change her life to be better and as a result everyone around her would respects her. Third, Jane Eyre is described as a portrait of an independent woman because of her financial independence and her independence of thinking and behaving. This study is expected to help readers to have understanding about the portrait of an Independent woman as reflected in the novel and be useful as a reference to the study of literature.